Muslim women leaders in Malaysian universities: Managing identities, power & institutions - Habibah Ismail; Hazleena Baharun; Suhaili A. Jalil; Sakinah Ahmad; Mohd Muzhafar Idrus; Haliza Harun (Universiti Sains Islam Malaysia, 2025)
Abqari Journal. Volume 32 Issue 2 Page (158–173)